The Joint Association of Sleep Quality and Outdoor Activity with Asthma and Allergic Rhinitis in Children: A Cross-Sectional Study in Shanghai - Lu R; Zhang Y; Chen Y; Lyu J; Li R; Kang W; Zhao A; Ning Z; Hu Y; Lin X; Tong S; Lu Z; et al. (Journal of Asthma and Allergy)
Ruoyu Lu,1,* Ye Zhang,1,* Yiting Chen,1 Jiajun Lyu,1 Rong Li,1 Wenhui Kang,1 Anda Zhao,1,2 Zidi Ning,1 Yabin Hu,3 Xiaya Lin,4 Shilu Tong,3 Zhaohui Lu,3 Shenghui Li1,5 1School of Public Health, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Huadong Hospital, Fudan University, Shanghai, People’s Republic of China; 3National Children’s Medical Center, Shanghai Children’s Medical Center, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 4Hainan Branch, Shanghai Children’s Medical Center, School of Medicine, Shanghai Jiao Tong University, Sanya, Hainan Province, People’s Republic of China; 5MOE-Shanghai Key Laboratory of Children’s Environmental Health, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhaohui Lu, National Children’s Medical Center; Shanghai Children’s Medical Center, School of Medicine, Shanghai Jiao Tong University, 1678 Dongfang Road, Pudong District, Shanghai, 200127, People’s Republic of China, Tel +86-18930830796, Email luzhaohui@sjtu.edu.cn Shenghui Li, School of Public Health, Shanghai Jiao Tong University School of Medicine, 227 South Chongqing Road, Huangpu District, Shanghai, 200025, People’s Republic of China, Tel +86-21-63846590, Email lsh9907@163.com; submission9907@163.comPurpose: Aiming to investigate the combined association of sleep quality and outdoor activity with the risk of asthma and allergic rhinitis in children.Patients and Methods: 16,936 children from kindergartens and primary schools in 13 administrative districts of Shanghai, China were involved in the analyses. The Children’s Sleep Habits Questionnaire (CSHQ) and the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire were respectively used to evaluate the sleep quality, allergic rhinitis and asthma. Multivariable logistic regression models were used to analyze the correlation of sleep quality, outdoor activities and their combination with children’s asthma and allergic rhinitis.Results: The overall prevalence of asthma and allergic rhinitis in our sampled children were 10.2% and 17.6%, respectively. Poor sleep quality (asthma: aOR, 1.45; 95% CI: 1.23 to 1.73; allergic rhinitis: aOR, 1.16; 95% CI: 1.03 to 1.31) and low outdoor activity (asthma: aOR, 1.30; 95% CI: 1.14 to 1.49, allergic rhinitis: aOR, 1.18; 95% CI: 1.07 to 1.32) were separately associated with higher risk of asthma and allergic rhinitis, and when the two were superimposed, an additive effect (asthma: aOR, 1.76; 95% CI: 1.30 to 2.39; allergic rhinitis: aOR, 1.46; 95% CI: 1.17 to 1.82) was revealed. These associations were independent of sleep duration, but being stronger in sleep sufficiency group. And after stratification by gender, premature birth and family history of allergy, similar associations were validated in general.Conclusion: Poor sleep quality and low levels of outdoor activity, when combined, have a stronger association with asthma and allergic rhinitis than each factor independently, and this relationship is not influenced by sleep duration. Our findings highlight the need for public health interventions that simultaneously address multiple lifestyle factors to reduce the risk of allergic diseases.Keywords: asthma, allergic rhinitis, sleep quality, physical activity